2020
DOI: 10.1097/shk.0000000000001596
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Postconditioning Inhibits Hippocampal Neuronal Apoptosis and Mitophagy After Cardiopulmonary Resuscitation in Rats

Abstract: Background: Studies have shown that remote ischemic post-conditioning can improve brain damage caused by ischemia and hypoxia. However, the specific mechanism underlying this phenomenon is still unclear. The purpose of this study was to investigate the effects of remote ischemic post-conditioning on neuronal apoptosis and mitophagy after cardiopulmonary resuscitation (CPR) in rats. Methods: Male Sprague-Dawley rats were used to establish an asphyxia cardiac arrest model by clamping the tracheal duct. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Autophagy, including mitophagy, is a tightly modulated cellular degradation process responsible for the clearance of damaged proteins and organelles 12 . Generally, excessive mitophagy brings about mitochondrial impairment and further triggers hippocampal neuron apoptosis via the death receptor pathway of endogenous 13 . An increasing number of studies also indicate the relationship between autophagy and apoptosis 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy, including mitophagy, is a tightly modulated cellular degradation process responsible for the clearance of damaged proteins and organelles 12 . Generally, excessive mitophagy brings about mitochondrial impairment and further triggers hippocampal neuron apoptosis via the death receptor pathway of endogenous 13 . An increasing number of studies also indicate the relationship between autophagy and apoptosis 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Generally, excessive mitophagy brings about mitochondrial impairment and further triggers hippocampal neuron apoptosis via the death receptor pathway of endogenous. 13 An increasing number of studies also indicate the relationship between autophagy and apoptosis. 14,15 It has been accepted that increased hippocampal neuron apoptosis plays an important role in the pathogenesis of diabetes-related depression.…”
Section: Introductionmentioning
confidence: 99%
“…It is predictable that iPostC regulates mitophagy, but the mechanisms involved are unknown. Some evidence supporting this argument comes from studies where remote ischemic postconditioning (RIPostC) inhibits the overactivation of mitophagy [190,191], or those in which Hyp-PostC and RIPostC promote mitophagy through the PINK1/Parkin pathway [192], providing neuroprotective effects against ischemia and hypoxia.…”
Section: Regulation Of Mitophagy By Cardiac Conditioningmentioning
confidence: 99%
“…Previous studies have shown that the activation of autophagy helps to improve the pathological damage caused by neurodegenerative and ischemic diseases. Autophagy induction has been found in both neonatal and adult rodents after HIBD, but its role in HIE is still controversial [ 7 , 34 ]. It has been reported that inhibition of autophagy aggravates neuronal mitochondrial dysfunction and aggravates apoptosis in HIBD pups [ 35 ].…”
Section: Introductionmentioning
confidence: 99%